SEXUAL EDUCATION IN SCHOOL CONTEXT: THE STRATEGIES USED IN THE CLASSROOM FOR TEACHERS - Nogueira, N. S.; Zocca, A. R. [UNESP]; Muzzeti, L. R. [UNESP]; Ribeiro, P. R. M. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2016)
Sexual education is a transversal theme in education and included in National Curricular Parameters (PCNs). This direction, the article aims to understand which learning materials on the subject to base teaching work in clarifying the questions of students in the classroom. Participated in the search six teachers of education of young adults, between 43 and 66 years old of a city in the state of Sao Paulo. The results showed that teachers know the terms sexuality and sexual education and they speak sexuality in the classroom. They used books, movies and dialogues in action and highlight the importance of sexual education in the prevention, breaking taboos and awareness of the students. Therefore, sexual education in school is relevant and pertinent, as well as, provides moments of reflection and learning.
Keywords: Teacher; Courseware; Sexual education